Factors that Motivates Management to Commit Fraudulent Financial Reporting - Mahanum, Sulaiman; Hasnah, Haron; Effiezal Aswadi, Abdul Wahab (Malaysian Institute of Corporate Governance, 2016)
The collapse of a number of companies as a result of accounting manipulation by managers has raised serious questions about the effectiveness of the monitoring mechanism to protect investors’ interests and control managerial opportunistic behaviour